2009
DOI: 10.1007/s00421-009-1034-5
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between monocarboxylate transporters 1 and 4 expression in skeletal muscle and endurance performance in athletes

Abstract: The purpose of this study was to examine the relationship between skeletal muscle monocarboxylate transporters 1 and 4 (MCT1 and MCT4) expression, skeletal muscle oxidative capacity and endurance performance in trained cyclists. Ten well-trained cyclists (mean +/- SD; age 24.4 +/- 2.8 years, body mass 73.2 +/- 8.3 kg, VO(2max) 58 +/- 7 ml kg(-1) min(-1)) completed three endurance performance tasks [incremental exercise test to exhaustion, 2 and 10 min time trial (TT)]. In addition, a muscle biopsy sample from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…Similarly, Thomas et al (144) have reported that fatigue indices measured during continuous, 1-min, all-out and intermittent (repeated 10-s cycling sprints interspersed with 30 s of recovery) supramaximal exercise, were inversely related to MCT1 content (r ϭ Ϫ0.54, P Ͻ 0.05 and r ϭ Ϫ 0.58, P Ͻ 0.05, respectively), but not MCT4 content, in 15 humans with different training status. Nevertheless, this result is in contrast to that obtained for lower-intensity exercise, since both MCT1 and MCT4 content in a homogeneous group of trained athletes was not correlated with performance when subjects were required to cycle at the highest sustainable power output for 2 and 10 min (9). As limited data are available in humans regarding MCT content and exercise performance, further research is required to investigate the effects of the population studied (homogeneous or heterogeneous, trained or untrained) and exercise intensity on the relationship between MCT content and exercise performance.…”
Section: Sarcolemmal Lactate/proton Cotransporters In Skeletal Musclecontrasting
confidence: 85%
“…Similarly, Thomas et al (144) have reported that fatigue indices measured during continuous, 1-min, all-out and intermittent (repeated 10-s cycling sprints interspersed with 30 s of recovery) supramaximal exercise, were inversely related to MCT1 content (r ϭ Ϫ0.54, P Ͻ 0.05 and r ϭ Ϫ 0.58, P Ͻ 0.05, respectively), but not MCT4 content, in 15 humans with different training status. Nevertheless, this result is in contrast to that obtained for lower-intensity exercise, since both MCT1 and MCT4 content in a homogeneous group of trained athletes was not correlated with performance when subjects were required to cycle at the highest sustainable power output for 2 and 10 min (9). As limited data are available in humans regarding MCT content and exercise performance, further research is required to investigate the effects of the population studied (homogeneous or heterogeneous, trained or untrained) and exercise intensity on the relationship between MCT content and exercise performance.…”
Section: Sarcolemmal Lactate/proton Cotransporters In Skeletal Musclecontrasting
confidence: 85%
“…There is a tendency for VO 2max and peak power output obtained in an incremental exercise test to be correlated with MCT1 expression. 13 MCT1 is a protein that in humans is encoded by the MCT1 gene (also known as SLC16A1; location: 1p12), the member of metabolic genes whose expression is regulated by PGC-1α in skeletal muscle. 14 Mutations in MCT1 cDNA were found in patients with rare condition known as cryptic exercise intolerance, in which otherwise healthy individuals suffer severe chest pain and muscle cramping on vigorous exercise.…”
mentioning
confidence: 99%
“…Katsuyuki, who is an employee of Blue Wych Limited Company, voluntarily participated in this study for experimental design and interpretation of results. The au-of high-intensity exercise 10,24) . These results suggest that MCT4 may be closely related to metabolism during highintensity exercise.…”
Section: Conflict Of Interestsmentioning
confidence: 99%
“…When transporting lactate from working muscles into the circulatory system, a membrane transport protein called monocarboxylate *Correspondence: hatta@idaten.c.u-tokyo.ac.jp transporter (MCT) 4 plays an important role 9) . David et al (2009) reported that MCT4 protein levels of working muscle were strongly correlated with the performance of high intensity exercise in well-trained cyclists 10) . Therefore, it was assumed that MCT4 plays an important role in performing high intensity exercise.…”
Section: Introductionmentioning
confidence: 99%